Answer:
multiplying both-side of the equation by 3
substituting 36 for p to check the solution
Step-by-step explanation:
To solve the equation p/3 = 12, we will follow the steps below;
first multiply 3 to both-side of the equation, that is:
p/3 × 3 = 12 × 3
On the left-hand side of the equation, 3 at the numerator will cancel-out 3 at the denominator, leaving us with just p while on the right-hand side of the equation 12 will be multiplied by 3
p= 36
To check the correctness of the equation, we can substitute p = 36 back into the equation and then check, that is;
p/3 = 12
36/3 = 12
This implies p = 36 is correct
Answer:
Step-by-step explanation:
There are 16 cups in a gallon
The square of a binomial expands as follows:

Expanding all the binomials, we have

Sum like terms:

Simplify terms appearing on both sides:

Move all terms involving k to the left and all numbers to the right:

Divide both sides by -20:
